2016
DOI: 10.1021/acs.nanolett.6b03582
|View full text |Cite
|
Sign up to set email alerts
|

Al–Pd Nanodisk Heterodimers as Antenna–Reactor Photocatalysts

Abstract: Photocatalysis uses light energy to drive chemical reactions. Conventional industrial catalysts are made of transition metal nanoparticles that interact only weakly with light, while metals such as Au, Ag, and Al that support surface plasmons interact strongly with light but are poor catalysts. By combining plasmonic and catalytic metal nanoparticles, the plasmonic "antenna" can couple light into the catalytic "reactor". This interaction induces an optical polarization in the reactor nanoparticle, forcing a pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
234
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 212 publications
(243 citation statements)
references
References 32 publications
3
234
0
1
Order By: Relevance
“…Other approaches have utilized top-down lithographic techniques, by which 2-dimensional films of photocatalysts were obtained. [38][39][40][41] Recently it has been shown that Pd nanoparticle-decorated, oxide-coated Al nanocrystals enable efficient plasmon-induced photocatalysis at the Pd surface, where the plasmonic and catalytic functions were effectively distinct. 42 This general structure has been called an "antenna-reactor" complex, where the plasmonic nanoparticle is the antenna and the catalytic particle, which can be interchanged based on desired reactivity, is the reactor.…”
Section: 33mentioning
confidence: 99%
See 1 more Smart Citation
“…Other approaches have utilized top-down lithographic techniques, by which 2-dimensional films of photocatalysts were obtained. [38][39][40][41] Recently it has been shown that Pd nanoparticle-decorated, oxide-coated Al nanocrystals enable efficient plasmon-induced photocatalysis at the Pd surface, where the plasmonic and catalytic functions were effectively distinct. 42 This general structure has been called an "antenna-reactor" complex, where the plasmonic nanoparticle is the antenna and the catalytic particle, which can be interchanged based on desired reactivity, is the reactor.…”
Section: 33mentioning
confidence: 99%
“…1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 17 all structures are illuminated with equal photon flux and the absorption efficiency by the film is much less than 100%, then ENH Abs provides a complete description of how significantly the Ag NP plasmonic near field will enhance Pt light absorption ( Figure S15). [38][39][40][41] However, in a 3-D catalyst bed operated in the light-limited regime, it is not enough to simply consider how much Ag enhances Pt light absorption in discrete heterostructures, and thus the relative magnitude of ENH Abs as a function of Ag particle size do not match the experimentally measured trends in photocatalytic rates (Figure 2). …”
Section: 33mentioning
confidence: 99%
“…For these reasons, it has been proposed to couple a plasmonic antenna directly to the catalytic nanoparticle. This antenna-reactor complex allows absorption enhancements in poorly light-absorbing catalytic metals [35]. The feasibility of these heterostructures has been demonstrated using Al as "antenna" and Pd as "reactor" heterodimers [35] and decorated spherical nanoparticles [36].…”
Section: Aluminummentioning
confidence: 99%
“…This antenna-reactor complex allows absorption enhancements in poorly light-absorbing catalytic metals [35]. The feasibility of these heterostructures has been demonstrated using Al as "antenna" and Pd as "reactor" heterodimers [35] and decorated spherical nanoparticles [36]. Aluminum-cuprous oxide antenna-reactor nanoparticles have also been proven to be an efficient photocatalytic heterostructure [37].…”
Section: Aluminummentioning
confidence: 99%
“…This suggests that localized plasmon resonances could form at the edges of finite MoS 2 flakes. The existence of such plasmon resonances could strongly influence the optical properties of the flakes and could potentially be of interest for plasmonic photocatalysis where hot electrons generated by the decay of plasmons are used to drive chemical reactions [20,21]. We note in passing that the plasmons in MoS 2 flakes have recently been studied by means of low-loss electron energy loss spectroscopy [22].…”
Section: Introductionmentioning
confidence: 99%